Combating Prejudice in the Workplace with Contact Theory: The Lived Experiences of Professionals with Disabilities - Harpur, Paul David (Disability Studies Quarterly, 2014)
People with disabilities often confront barriers in exercising their right to work. Social model scholarship has recognised that attitude is a key factor in the disablement of people with impairments. This study reports on 28 semi-structured interviews with professionals with disabilities. Drawing from their lived experiences and roles in the disability rights movement, the professionals with disabilities interviewed in this study provide unique perspectives on the instances of attitudinal discrimination. The interviewees discuss the tactics they employ to reduce the negative impact of erroneous stereotypes and the successes of such tactics. Many of the tactics employed by interviewees reflect strategies discussed in contact theory scholarship. This study focuses upon contact theory and considers the similarities between this theory and the interventions of interviewees. Through positing interviewees' tactics in the literature this study is able to analyse possible positive and negative consequences of such interventions. Keywords: Contact theory, right to work, professionals with disabilities